Characterization of facial burns from maxillofacial surgery. Cienfuegos 2005 - 2007 - Eduardo Duarte Marrero; Patricia Cristina Jiménez Beato (Medisur, 2010)
Background: A descriptive study and retrospective study with 87 patients for facial burns, were treated at the Burn Service of the Hospital General Universitario "Dr. Gustavo Lima Aldereguía "Cienfuegos between January 2005 and September 2007. Objective: To characterize the care of patients with facial burns to help develop knowledge, attitudes and skills medical - surgery in the maxillofacial surgeon. Method: the source of information used were the records of patient care in the emergency department Burned Service and these data were selected that identified the patients as well as other related directly with facial burns. For each patient, more severe burning classified according to their size and depth. Results: In this study facial burns were more frequent in females aged 16 to 34 years, the most common cause of these lesions was in contact with boiling liquids as the predominant type skin burns, with extensions between 2 and 4% of the face area. In 44 patients affected centers facial structures, so predominant involvement of the ears. The priest most used in the facial region was the stop with silver sulfadiazine. Approximately 50% of patients were affected in the organs of sense, particularly in the ears. Conclusion: The traumatic facial burns are more severe conditions than any other location for the possible commitment to the airways.